The Impact of SMART Media Technologies (SMT) on the Spiritual Experience of Hajj Pilgrims - Qurashi, Jahanzeeb (The international journal of religious tourism and pilgrimage, 2018)
Over the last three decades, information and communication technologies have advanced rapidly and continue to do so. Nowadays, the popularity and spread of socalled Smart Media Technologies (SMT) is not only transforming the lives of tourists around the world in general, but is impacting on the experience of pilgrims on the Hajj in Saudi Arabia in particular. Indeed, the Saudi government has undertaken a number of initiatives to encourage the use of SMT in the religious tourism industry. Specifically, the availability of SMT services such as Hajj Apps, E-bracelets for pilgrims, free WIFI and mobile charging services in Grand Mosques (in both Makkah and Madinah), dedicated social media websites, and the ability of pilgrims to take advantage of smartphone activities are facilitating and enhancing their technological and social experience of the Hajj. However, the introduction of high-tech' into the Hajj is arguably impacting on the nature of the pilgrims' experience, challenging its fundamental spirituality by transforming it into something more akin to a cyber experience', an experience which competes with and jeopardises the principles of the Islamic religious journey of the Hajj with its focus on worship, simplicity and nonostentatious behaviour. Therefore, the purpose of this paper is to explore how the spiritual experience of pilgrims may be influenced by the availability and use of various SMT services. The findings suggest ways in which these technological services both enhance and impact negatively on the pilgrim's spiritual experience.